An Investigation Into Students' Challenges In Comprehending Islamic English Short Stories - Khairunnisa; Santoso, Didik; Daulay, Sholihatul Hamidah (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to find out the students' challenges in comprehending Islamic English short stories and how they are presented. The data for this study was gathered through qualitative methods by utilizing interviews, observations, and documentation. One student from MTS Pondok Pesantren Darul Hikmah Taman Pendidikan Islam Medan took part in the study. After analyzing the data, the researcher discovered that the students' challenges in comprehending Islamic English short stories are divided into five categories: (1) The challenge in understanding the word, where the student could not understand certain vocabularies in the story and needed to use a dictionary; (2) the challenge in combining the words into sentences, where the student could not arrange the translated vocabularies in a logical order; (3) the challenge in coherency, in which the student was unable to translate the translated words into a logical translation; (4) the challenge in reading speed, in which the student was unable to track the important points of the text quickly; and (5) the challenge in inferencing, in which the student was unable to make a perfect conclusion to the story.